Natural Anti-Inflammatory Compounds as Drug Candidates for Inflammatory Bowel Disease - Duan, Linshan; Cheng, Shuyu; Li, Long; Liu, Yanling; Wang, Dan; Liu, Guoyan (Frontiers in Pharmacology, 2021)
Inflammatory bowel disease (IBD) represents chronic recurrent intestinal inflammation resulting from various factors. Crohn’s disease (CD) and ulcerative colitis (UC) have been identified as the two major types of IBD. Currently, most of the drugs for IBD used commonly in the clinic have adverse reactions, and only a few drugs present long-lasting treatment effects. Moreover, issues of drug resistance and disease recurrence are frequent and difficult to resolve. Together, these issues cause difficulties in treating patients with IBD. Therefore, the development of novel therapeutic agents for the prevention and treatment of IBD is of significance. In this context, research on natural compounds exhibiting anti-inflammatory activity could be a novel approach to developing effective therapeutic strategies for IBD. Phytochemicals such as astragalus polysaccharide (APS), quercetin, limonin, ginsenoside Rd, luteolin, kaempferol, and icariin are reported to be effective in IBD treatment. In brief, natural compounds with anti-inflammatory activities are considered important candidate drugs for IBD treatment. The present review discusses the potential of certain natural compounds and their synthetic derivatives in the prevention and treatment of IBD.